Evolving the common agricultural policy for tomorrow's challenges - Détang-Dessendre, Cécile; Guyomard, Hervé (éditions Quae, 2023)
As in other parts of the world, agriculture in Europe is not sustainable. It must urgently and importantly evolve. The Common Agricultural Policy (CAP) must foster this evolution. In that perspective, this book draws the contours of an ambitious CAP that would facilitate the necessary agro-ecological transition of agricultural systems in the European Union. The book is divided into three parts. The economic aspects are the subject of the first part. The climate, environmental and health dimensions are addressed in the second part. The third part deals with rural development and innovation. With the exception of the first chapter, which provides a brief history of the CAP, the different chapters are organized according to the same structure. They begin with a description of the issue; they continue with a critical presentation of how the issue has been considered within the CAP to date and, if relevant, in other public policies; they finally propose policy recommendations to better address the issue. Each chapter can be read independently. Even if the disciplines and skills mobilized cover a broad spectrum, the general framework of analysis is that of public economics. This reading key is used both to justify the objectives of the CAP and to define the policy instruments to be implemented in order to achieve these objectives in the most efficient way. The concluding chapter addresses three aspects: first, an analysis of the global coherence of our recommendations, including in terms of their links with other policies than the CAP; second, a critical reading of the June 2021 agreement for the 2023-2027 CAP in the light of our recommendations; third, a reading of our recommendations in the light of the ambition of the European Green Deal for agriculture and food. This book is aimed at all actors interested in the future of the CAP and more generally of agriculture in the European Union: policy makers, agricultural stakeholders, non-governmental organizations, researchers, teachers and students.